Multi-objective optimization of a flux switching wound field machine using a response surface-based multi-level design approach - Chiweta E. Abunike; Milad Dowlatshahi; Aliakbar Jamshidi Far; Ogbonnaya I. Okoro; Sumeet S. Aphale (Results in Engineering)
This study introduces a novel multilevel design optimization approach for enhancing the performance of brushless flux-switching wound-field machines (FSWFMs) in electric vehicles (EVs) and industrial drives. The proposed methodology targets key performance metrics namely, high torque, efficiency, power factor, and low torque ripple through a structured sensitivity analysis categorized into non-sensitive, mild-sensitive, and strong-sensitive levels. Using the Response Surface Method (RSM), Min-Max Search, and Multi-Objective Genetic Algorithms (MOGA), the Response Surface Multi-Level Optimization (RSMLO) method effectively harmonizes these competing objectives. The optimization process resulted in an 11% increase in average torque and a 69.06% reduction in torque ripple, demonstrating significant performance gains. These results underscore the potential of the RSMLO method as a robust tool for the advanced design of electric machines, offering substantial improvements in both performance and efficiency, and positioning it as a critical framework for future EV and industrial drive applications.